Answer:
1/5 and -k/5+2
Step-by-step explanation:
inverse of 5= 1/5
swap the variables: y=10−5k becomes k=10−5y
Now, solve the equation k=10−5y
for y
y=−k/5+2
Answer: 55
Step-by-step explanation:
![\sqrt[3]{4x-4}=6](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B4x-4%7D%3D6)
Begin by cubing each side of the equation to get rid of the cubic root.
![(\sqrt[3]{4x-4})^3=(6)^3\\ 4x-4=216](https://tex.z-dn.net/?f=%28%5Csqrt%5B3%5D%7B4x-4%7D%29%5E3%3D%286%29%5E3%5C%5C%204x-4%3D216)
add 4

Divide by 4


Answer:
x = 22.45
Step-by-step explanation:
Have a good day :)
Answer:
-4
Step-by-step explanation:
'cause yan Ang answer